Validação e aplicação do sequenciamento de nova geração para pesquisa de variantes genéticas em neoplasias mieloides e relação com o prognóstico da doença. - Fabiana Kalina Marques (2023)
Myeloid neoplasms comprise biologically distinct subtypes of hematologic malignancy, with different clinical, genetic, and design features. Knowledge of the genetic basis of NMs has increased rapidly, especially after the development of next-generation sequencing. Studies demonstrate that genetic similarities between morphologically distinct diseases are associated with the presence of recurrent variants affecting cellular pathways grouped into functional categories. In this way, the analytical performance of the OncomineTM Myeloid panel was evaluated, which allows the search for variants in 40 target genes, gene fusions involving 29 driver genes, and analysis of the relative expression of five genes, by nextgeneration sequencing. Among the 34 sequenced clinical samples, 29 (85.2%) identified at least one variant. A total of 63 variants were detected: 33 single nucleotide variants, 24 indels and six gene fusions. Our cohort's most frequently mutated genes were TET2, IDH2, FLT3, and ASXL1. There was a difference in gene expression for the BAALC and WT1 genes when compared to the acute myeloid leukemia, myelodysplastic neoplasm, and myeloproliferative neoplasm groups. A difference was observed in the platelet-lymphocyte ratio when comparing the three groups. A difference in survival was observed in the cohort regarding variants in the FLT3 and TP53 genes and the number of variants detected per sample. The OncomineTM Myeloid panel demonstrated high sensitivity, specificity, and reproducibility in the detection of variants relevant to the investigation of myeloid neoplasms. This study demonstrated the relevance of molecular profiling in myeloid neoplasms by next-generation sequencing panels for the diagnosis and risk stratification of these diseases, especially in acute myeloid leukemia and myelodysplastic neoplasm. Additional studies in larger samples are needed to better evaluate the contribution of gene expression analyses and the platelet-lymphocyte, neutrophil-lymphocyte, and monocytelymphocyte ratios for the diagnosis and prognosis of myeloid neoplasms.